(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article discusses the factors that influenced the formation of stylistic canons in English prose of the second half of the seventeenth century. This period is characterized by the formation of English literature national language norms, when philosophical, lyrical, emotional, intellectual understanding of life changes took place and the battle in the literature over the new style, designed to reflect the dynamics of the inner life of man has begun. Being investigated the stylistic influence and signs of the new style in connection with principal literary direction of epoch – classicism. Attention is drawn to rational-logical direction of this style. The essays of the second half of the XVII century being examined, as an intermediate genre that occurs at the intersection of literature, journalism and philosophy. Special attention is paid to small epic forms (essays, meditations, diaries), specific language which is dictated by the General structural peculiarities of this prose, strictly rational-logically and rhetorically organized. A significant part of the prose, the period under investigation, represented the argumentative – texts focused on traditional forms of rhetorical prose of antiquity. The formation of a new stylistic canons in English prose of the XVII century, orienting the tastes on logical and stylistic clarity, is inextricably linked with the appeal to classical models. Ancient rhetoric had a huge impact on the formation of the style of English prose. Particularly important is one of the components of ancient rhetoric – style. The struggle for a new style, simple and natural especially widely and pointedly turned around in this period in ecclesiastical literature. Publishing of huge numbers of sermons implied the existence of readers. They were valued not only for instruction but also as a model of rhetoric and oratory. In literature flood plain words, verbal structures and conversational intonations. Among the significant reasons that influenced the development of prose of the period, marked – impact of journalism, the revival of political struggle, expressed in the sharp political debate, rationalist approach to the language generated by a philosophy of rationalism. The evolution of prose style in the second half of the XVII century was subordinated to the chief – the creation of the truthfulness and ease of communicating ideas. The element of reasoning covered the whole of the prose, the sermons, treatises, essays. The general stylistic requirements of English prose have been formulated.